2005
DOI: 10.1111/j.1600-0897.2005.00290.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Macrophage Colony Stimulating, Vascular Endothelial, and Placenta Growth Factor in Relation to Later Clinical Onset of Pre‐Eclampsia and a Small‐for‐Gestational Age Birth

Abstract: Depending on which growth factor is found to be reduced, an early distinction can be made in terms of an increased risk for PE or FGR. Inconsistencies in the literature may reflect differences in PE disease severity between studies and the presence of a varying fraction of cases with FGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 25 publications
1
23
1
1
Order By: Relevance
“…The kit used for the VEGF measurements of this study was R&D Systems, and the manufacturer guarantees the absence of interference or cross-reactivity with other VEGF isoforms, such as VEGF D, VEGF-C, and PlGF. As in the study of Bersinger and Odegard [26], the present study found no statistically significant differences between serum concentrations of normotensive pregnant women and those with PE and also did not allow for differentiation of the severity of PE in relation to proteinuria and gestational age.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The kit used for the VEGF measurements of this study was R&D Systems, and the manufacturer guarantees the absence of interference or cross-reactivity with other VEGF isoforms, such as VEGF D, VEGF-C, and PlGF. As in the study of Bersinger and Odegard [26], the present study found no statistically significant differences between serum concentrations of normotensive pregnant women and those with PE and also did not allow for differentiation of the severity of PE in relation to proteinuria and gestational age.…”
Section: Discussioncontrasting
confidence: 69%
“…Some studies have observed increased VEGF serum levels [25], whereas others have observed reduced levels [3,7,19,24] and still others have found no significant differences when comparing pre-eclamptic and normotensive pregnant women [26]. These divergent results can be explained by methodological errors, different techniques for VEGF measurement in relation to the physical state of cytokines (whether circulating or proteinbound) and even the measurement of different VEGF isoforms.…”
Section: Discussionmentioning
confidence: 91%
“…The concentrations of PAPP-A, pregnancy-specific β1-glycoprotein (SP1), human placental lactogen (HPL), VEGF, and macrophage colony-stimulating factor (M-CSF) in the same sera were available from previous projects [11,14] investigating their usefulness for second-trimester risk assessment for subsequent PE to occur; they were used as backup data. Similarly the results for leptin, soluble endothelial (sE-) selectin, and insulin-like growth factor-binding protein 1 (IGF-BP1) were available after measurements using the methods previously applied to the third trimester [15].…”
Section: Methodsmentioning
confidence: 99%
“…In humans, low levels of PlGF have been associated with pre-eclampsia (25)(26)(27)(28)(29)(30), and endometrial PlGF is reported to be an exclusive product of uNK cells in the late menstrual cycle. PlGF is also found in uNK cells from early, elective pregnancy terminations (5).…”
Section: Discussionmentioning
confidence: 99%